Production of oil palm under phosphorus, potassium and magnesium fertilization - Matos Viégas, Ismael de Jesus; Dias dos Santos, Laura; Garcia Costa, Milton; de Oliveira Ferreira, Eric Victor; da Silva Barata, Henrique; Almeida Seabra Silva, Diocléa (Revista Ceres, 2023)
Oil palm production is strategic in the Amazon with high productive potential, but information on its fertilization is still relatively scarce for the region. The objective of this work was to evaluate the effects of phosphorus, potassium and magnesium fertilizations on oil palm production in different years in the state of Pará, Brazil. The study was conducted in Tailândia, Northeastern of Pará, Eastern Amazon, Brazil. A randomized block design was used in a 4 x 2 x 3 x 2 factorial scheme, with four levels of phosphorus, two sources of phosphorus, three levels of potassium and two levels of magnesium. Oil palm production responded positively to the increase in phosphorus levels, and until the eighth year of age of the plants, there was greater production when triple superphosphate was applied. From the ninth year onwards, fertilization with phosphine provided a production equal to the supply of phosphorus with triple superphosphate. The application of potassium chloride increased the number, weight and production of the bunches from the sixth year. The supply of magnesium sulfate increased the average weight of the bunches. Thus, phosphorus, potassium and magnesium fertilizations become essential to increase oil palm production in the Northeast of Pará.